Use of and confidence in administering outcome measures among clinical prosthetists: Results from a national survey and mixed-methods training program. (August 2015) - Gaunaurd, Ignacio; Spaulding, Susan E; Amtmann, Dagmar; Salem, Rana; Gailey, Robert; Morgan, Sara J; Hafner, Brian J
Background: Outcome measures can be used in prosthetic practices to evaluate interventions, inform decision making, monitor progress, document outcomes, and justify services. Strategies to enhance prosthetists' ability to use outcome measures are needed to facilitate their adoption in routine practice. Objective: To assess prosthetists' use of outcome measures and evaluate the effects of training on their confidence in administering performance-based measures. Study design: Cross-sectional and single-group pretest–posttest survey. Methods: Seventy-nine certified prosthetists (mean of 16.0 years of clinical experience) were surveyed about their experiences with 20 standardized outcome measures. Prosthetists were formally trained by the investigators to administer the Timed Up and Go and Amputee Mobility Predictor. Prosthetists' confidence in administering the Timed Up and Go and Amputee Mobility Predictor was measured before and after training. Results: The majority of prosthetists (62%) were classified as non-routine outcome measure users. Confidence administering the Timed Up and Go and Amputee Mobility Predictor prior to training was low-to-moderate across the study sample. Training significantly (p < 0.0001) improved prosthetists' confidence in administering both instruments. Conclusion: Prosthetists in this study reported limited use of and confidence with standardized outcome measures. Interactive training resulted in a statistically significant increase of prosthetists' confidence in administering the Timed Up and Go and Amputee Mobility Predictor and may facilitate use of outcome measures in clinical practice. Clinical relevance: Frequency of outcome measure use in the care of persons with limb loss has not been studied. Study results suggest that prosthetists may not regularly use standardized outcome measures and report limited confidence in administering them. Training enhances confidence and may encourage use of outcome measures in clinical practice.